2017
DOI: 10.1080/14786435.2017.1281461
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic details of precipitates in lean Al–Mg–Si alloys with trace additions of Ag and Ge studied by HAADF-STEM and DFT

Abstract: Bonding energies and volume misfits for alloying elements and vacancies in multicomponent Al-Mg-Si alloys have been calculated using density functional theory and the results have been compared with numbers obtained by atomic scale precipitate structure analysis, using high angle annular dark-field scanning transmission electron microscopy. The techniques in combination provide new insight into precipitation in these alloys. In the Ge containing alloy were found two new stacking configurations of the well-know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…The quaternary GBP has a lattice parameter larger than that of Q′ phase in Al-Mg-Si-Cu alloys. E. A. Mørtsell [34] and T. Saito [30] Although the influence of Ag on the precipitation of Al-Mg-Si alloys has been investigated by different researchers, most of these works focus on one single precipitate (such as β′ phase) in a given aging condition.…”
Section: Introductionmentioning
confidence: 99%
“…The quaternary GBP has a lattice parameter larger than that of Q′ phase in Al-Mg-Si-Cu alloys. E. A. Mørtsell [34] and T. Saito [30] Although the influence of Ag on the precipitation of Al-Mg-Si alloys has been investigated by different researchers, most of these works focus on one single precipitate (such as β′ phase) in a given aging condition.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the enhanced age hardening response of Al-Mg-Si alloys by microalloying with various elements is closely related to the modified precipitation sequence [9,[12][13][14][18][19][20]. For example, Cu can suppress the precipitation of β" and facilitate the formation of Cu-containing precipitates (e.g.…”
mentioning
confidence: 99%
“…Q', C and L [1]) [9,18]. Ge atoms were reported to substitute some of the Si atoms in β" due to the similar electronic properties between Ge and Si [12,19]. Li preferentially occupies Mg3 sites in the β" structure [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One unit cell has two such Si4Mg4-xAl2+x units at the (00z) and (½, 0, z+½) special positions in the unit cell. They may be regarded as molecular units of β" and were recently shown to come in three different stacking variations [11], sometimes mixed. The stacking variations occur particularly frequently with small additions of Ge, where Ge (partially) occupies some Si columns.…”
Section: Introductionmentioning
confidence: 99%